Разработка базы данных для автоматизации контроля, установки и обслуживания дорожных знаков - Svetlana Anatolyevna Zyryanova; Olga Alekseevna Filimonova (Вестник СибАДИ, 2017)
The necessity of the use of automated accounting for the installation and maintenance of traffic signs, providing timely planning, verification of operational status, replacement and maintenance of technical means of traffic management. The description of the structure, interface and database options, perform an automated count of the number, types, locations, dates, warranty periods installation of traffic signs on the road network of settlements.